Innovative PDS Partnerships for Effective Teaching and Learning - Balch, Bradley (Educational (Re)naissance, 2013)
Would you like to breathe energy into your university-school district partnership? At Indiana State University (ISU), two clinical immersion imperatives and four partnership contexts provide an innovative focus that adds deeper meaning and intentionality to educator preparation. Our educator preparation programs had been migrating to more clinically intensive programming for several years, but the support of our K-12 partners was essential if we were to emphasize early and continuous clinical teaching experiences to enhance preparation efforts. As a first step, we developed the distinctive Teachers of Tomorrow Advancing Learning (TOTAL) internship for elementary and special education majors and an immersion program for secondary and all-grades majors.